2018
DOI: 10.1002/14651858.cd010038.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face interventions for informing or educating parents about early childhood vaccination

Abstract: BackgroundEarly childhood vaccination is an essential global public health practice that saves two to three million lives each year, but many children do not receive all the recommended vaccines. To achieve and maintain appropriate coverage rates, vaccination programmes rely on people having sufficient awareness and acceptance of vaccines.Face‐to‐face information or educational interventions are widely used to help parents understand why vaccines are important; explain where, how and when to access services; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
2
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(161 citation statements)
references
References 122 publications
(317 reference statements)
8
122
2
11
Order By: Relevance
“…All of the interventions in this review were delivered via face‐to‐face approaches, and most ( n = 11) were delivered in North America. Although face‐to‐face intervention delivery approaches offer the potential for interaction, real‐time discussion, and peer support (e.g., Kaufman et al, ), intervention scalability is also important to consider in determining their wider potential impact and value. Logistic, resource, and fidelity concerns are common challenges when delivering face‐to‐face interventions on a larger scale (e.g., Milat, King, Bauman, & Redman, ).…”
Section: Discussionmentioning
confidence: 99%
“…All of the interventions in this review were delivered via face‐to‐face approaches, and most ( n = 11) were delivered in North America. Although face‐to‐face intervention delivery approaches offer the potential for interaction, real‐time discussion, and peer support (e.g., Kaufman et al, ), intervention scalability is also important to consider in determining their wider potential impact and value. Logistic, resource, and fidelity concerns are common challenges when delivering face‐to‐face interventions on a larger scale (e.g., Milat, King, Bauman, & Redman, ).…”
Section: Discussionmentioning
confidence: 99%
“…A few interventions have attempted to educate parents to encourage them to comply with vaccination, which follow a ‘knowledge‐deficit’ approach (Dubé et al ; Dubé et al ). Such interventions span from face‐to‐face interactions for educating or informing parents about early childhood vaccination (Ryman et al ; Saeterdal ; Kaufman et al ) to mass media campaigns to promote vaccination uptake (Shea et al ). Similar to the themes of the broader noncompliance literature, additional studies of noncompliance with childhood immunizations draw on factors that have been found to influence parents’ vaccination hesitance and recommend what government should or could do to enhance compliance (e.g., Dubé et al ).…”
Section: Public Noncompliance With Childhood Immunizationmentioning
confidence: 99%
“…Recently, the focus has shifted towards exploring particular communication strategies, even though this work is still in its infancy (Kaufman et al, 2013). The logic of this shift is that effective interaction can address concerns about vaccines and increase parents' motivation; on the other hand, poor communication from a pediatrician can "tip" a hesitant parent towards refusal or fail to motivate a cautious parent towards acceptance (Leask et al, 2012).…”
Section: Pediatricians and Effective Communication With Parentsmentioning
confidence: 99%